2017
DOI: 10.14505/jemt.v8.8(24).10
|View full text |Cite
|
Sign up to set email alerts
|

Cashless Payment in Tourism. An Application of Technology Acceptance Model

Abstract: Technology has given a profound impact on how tourism industry develops in the recent decades. One of the important technology advancement area is cashless payment system. It has been suggested that cashless payment system can enhance tourism experience and provide competitive advantage to market destinations. Currently, governments are actively promoting a cashless society in tourism sector. However, the study of the acceptance of tourists on cashless payment technology in destinations is still rarely found. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Customers must have confidence in cashless payment systems in order to embrace them. Past research has shown that cashless payment systems may actually increase efficiency and save time (Wulandari, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Customers must have confidence in cashless payment systems in order to embrace them. Past research has shown that cashless payment systems may actually increase efficiency and save time (Wulandari, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…PE is the best indication of consumers’ technology adoption intents and viewpoints according to our research (Venkatesh et al, 2012). PE or its representative constructs strongly correlate with customers’ views in many global e-banking surveys (e.g., Alaeddin et al, 2018; Bailey et al, 2017; Wulandari, 2017). Aslam et al (2017) and Tian and Dong (2013) investigated Chinese and Pakistani mobile payment services.…”
Section: Performance Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…Studi yang dilakukan di Timur Tengah menemukan pengaruh positif performance expectancy terhadap sikap konsumen dalam penggunaan layanan mobile banking (Patil et al, 2020). Performance expectancy berpengaruh positif terhadap sikap penerimaan pembayaran non-tunai (Nuri Wulandari, 2017). Selanjutnya, penelitian terdahulu juga mengungkapkan bahwa performance expectancy merupakan faktor penting dalam mendorong sikap positif dalam penggunaan layanan digital (Hamzat & Mabawonku, 2018).…”
Section: Performance Expectancy Terhadap Attitude Dan Behavioral Inte...unclassified
“…Cevik, 2020; Kraenzlin et al , 2020; Barabas and Schmidt, 2021; Khanra et al , 2021). Also, the cashless payment system can enhance the tourist experience and provide a competitive advantage to market destinations (Wulandari, 2017; Ozturk, 2016; Miniaoui et al , 2019). In the future, also due to the expected launch of CBDC (Turkay et al , 2019), digital payment infrastructure will be a fundamental asset for tourism.…”
Section: Literature Reviewmentioning
confidence: 99%